Transmembrane Protein Ttyh1 Maintains the Quiescence of Neural Stem Cells Through Ca2+/NFATc3 Signaling - Cao, Yuan; Wu, Hai-ning; Cao, Xiu-li; Yue, Kang-yi; Han, Wen-juan; Cao, Zi-peng; Zhang, Yu-fei; Gao, Xiang-yu; Luo, Ceng; Jiang, Xiao-fan; Han, Hua; Zheng, Min-hua (Frontiers in Cell and Developmental Biology, 2021)
The quiescence, activation, and subsequent neurogenesis of neural stem cells (NSCs) play essential roles in the physiological homeostasis and pathological repair of the central nervous system. Previous studies indicate that transmembrane protein Ttyh1 is required for the stemness of NSCs, whereas the exact functions in vivo and precise mechanisms are still waiting to be elucidated. By constructing Ttyh1-promoter driven reporter mice, we determined the specific expression of Ttyh1 in quiescent NSCs and niche astrocytes. Further evaluations on Ttyh1 knockout mice revealed that Ttyh1 ablation leads to activated neurogenesis and enhanced spatial learning and memory in adult mice (6 – 8 weeks). Correspindingly, Ttyh1 deficiency results in accelerated exhaustion of NSC pool and impaired neurogenesis in aged mice (12 months). By RNA-sequencing, bioinformatics and molecular biological analysis, we found that Ttyh1 is involved in the regulation of calcium signaling in NSCs, and transcription factor NFATc3 is a critical effector in quiescence versus cell cycle entry regulated by Ttyh1. Our research uncovered new endogenous mechanisms that regulate quiescence versus activation of NSCs, therefore provide novel targets for the intervention to activate quiescent NSCs to participate in injury repair during pathology and aging.